Altered lipoproteins in patients with systemic lupus erythematosus are associated with augmented oxidative stress: a potential role in atherosclerosis. Issue 1 (December 2016) - Park, Jin; Kim, Jae-Yong; Moon, Jin; Ahn, Eun; Lee, Eun; Lee, Eun; Cho, Kyung-Hyun; Song, Yeong
Abstract Background To examine the structural and oxidative properties of lipoproteins from patients with systemic lupus erythematosus (SLE). Methods The lipid profiles of 35 SLE patients and 15 healthy controls (HCs) were compared. Oxidation status, susceptibility to oxidation, and structural integrity of low-density lipoprotein (LDL) were determined by measuring malondialdehyde (MDA), de novo formation of conjugated dienes in the presence of CuSO4, and mobility on gel electrophoresis, respectively. In vitro foam cell formation and the oxidative potential in zebrafish embryos were examined. Results LDL levels in SLE patients and HCs were similar (p  = 0.277). LDL from SLE patients was more fragmented than that from HCs. In addition, LDL from SLE patients was more oxidized than LDL from HCs (p  < 0.001) and more susceptible to de novo oxidation (p  < 0.001) in vitro. THP-1 cells engulfed more LDL from SLE patients than LDL from HCs (p  < 0.001). LDL from SLE patients, which was injected into zebrafish embryos, induced a higher degree of oxidation and a higher mortality than LDL from HCs (bothp  < 0.001). The survival of embryos treated with oxidized LDL was significantly better in the presence of HDL3 from HCs than that from SLE patients (allp  < 0.001). Conclusions Lipoproteins from SLE patients exhibited greater oxidative potential, which might contribute to accelerated atherosclerosis in SLE.